Combined experimental and multiphase computational fluid dynamics analysis of surface textured journal bearings in mixed regime of lubrication. (31st January 2018) - Morris, N.J.; Shahmohamadi, H.; Rahmani, R.; Rahnejat, H.; Garner, C.P.
Abstract: This paper investigates the effect of surface texturing in a partial pad journal bearing through a series of controlled experiments at operating conditions, promoting mixed or boundary regimes of lubrication. Improvements to load carrying capacity are observed under certain operating conditions. A comprehensive computational finite volume multiphase fluid dynamics analysis, including vapour transport equation and modified finite‐size cavity Rayleigh‐Plesset model, is used to study the effect of indented surface textures in the microscale contact domain and within the individual textures themselves. The results show improved conditions with a textured journal through promotion of micro‐hydrodynamic effect, delaying the effect of lubricant rupture, thus extending the effective load bearing region. A very good agreement is obtained between measurements and predictions.